PENGUATAN IDENTITAS NASIONAL ANAK PEKERJA MIGRAN INDONESIA DI MALAYSIA MELALUI PEMBELAJARAN BUDAYA DAN PATRIOTISME - Divana, I Gusti Aliyah; Azkiana, Zuhra; Sukma, Shandyka Naraya; Martha, Ardhya Farisha; Fiqli, Fatkan Nur; Nurhidayanti, Raf'a; Nugroho, Muhamad Dzaky Anandita; Martak, Samara Claire; Ananingati, Raissa Maheswari; Farh, Febriana Maula; Azizah, Siti Nur (CV. Alina, 2024)
Pengabdian program